ANALISIS TINGKAT KEBANGKRUTAN SEBELUM DAN SAAT PANDEMI DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE DAN SPRINGATE S-SCORE (STUDI KASUS PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA 2016-2020) - Aadilah, Salmaa Rif’at; Hadi, Teguh Parmono (Dinamika Akuntansi Keuangan dan Perbankan, 2022)
This study aims to determine the difference in results in predicting bankruptcy using the Altman Z-Score model and the Springate S-Score model, as well as ineasures which model is most accurate in predicting bankruptcy at retail companies at Indonesia. The population used in this study are retail companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period with a sample of 11 companies. The sampling method used in this study was purposive sampling. The data analysis technique used multiple discriminant analysis. The results showed that there were differences in the results in predicting bankruptcy before and during the pandemic. Based on the two measurement methods used, before the pandemic there were 4 companies that were declared bankrupt and 7 companies that were declared healthy. During the pandemic, 8 companies were declared bankrupt and 3 companies were declared healthy. The bankruptcy model that has the highest level of accuracy is the Springate S-Score.